2021
DOI: 10.1097/md.0000000000026131
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL-6 and procalcitonin are two promising novel biomarkers for evaluating the severity of COVID-19 patients

Abstract: To evaluate the development of coronavirus disease 2019 (COVID-19), the roles of interleukin 6 (IL-6) and procalcitonin (PCT) were assessed to diagnose severe COVID-19. Between January and February 2020, 100 consecutive patients with confirmed COVID-19 were included and divided into common (n = 56), severe (n = 28), and critical (n = 16) groups. IL-6 and PCT levels were assayed and compared among groups. IL-6 levels were significantly different among groups (common, 23.93±9.64 pg/mL; seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Our findings revealed that elevated procalcitonin was most strongly associated with both mortality and ICU acceptance, thereby contributing to the growing body of evidence for the utility of procalcitonin in the context of COVID-19 infection [14,15]. Calcitonin is normally expressed in neuroendocrine cells, but its precursor, procalcitonin (PCT), has been identified as a unique biomarker specific for bacterial sepsis [16].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our findings revealed that elevated procalcitonin was most strongly associated with both mortality and ICU acceptance, thereby contributing to the growing body of evidence for the utility of procalcitonin in the context of COVID-19 infection [14,15]. Calcitonin is normally expressed in neuroendocrine cells, but its precursor, procalcitonin (PCT), has been identified as a unique biomarker specific for bacterial sepsis [16].…”
Section: Discussionmentioning
confidence: 56%
“…One meta-analysis demonstrated that elevated procalcitonin levels were linked with a 5-fold increased risk of severe COVID-19 infection [22] while another found that elevated procalcitonin, elevated D-dimer, and thrombocytopenia were all associated with severe infection [23]. Similarly, a study from China revealed correlations of IL-6 and procalcitonin levels with COVID-19 severity [14], namely that those with the highest levels of these two biomarkers exhibited significantly increased disease severity. Moreover, a meta-analysis of 25 studies with 5350 patients found that elevated procalcitonin levels were associated with an increased composite poor outcome [RR 3.92 (2.42, 6.35), p < 0.001; I 2 : 85%].…”
Section: Discussionmentioning
confidence: 99%
“…The mean IL-6 levels were recorded to be significantly higher in patients with severe COVID-19 compared with non-severe COVID-19 patients [15,16,[88][89][90][91][92][93][94]. Additionally, IL-6 was also reported as an independent predictor of ICU admission [95].…”
Section: Discussionmentioning
confidence: 92%
“…IL-6 increases the leukocyte migration to areas of inflammation, increases the division of B cells that produce antibodies, and plays a role in Th17 differentiation in T cells [80] (pp. [85][86][87]92). IL-6 activates the intracellular cascade of Jak/STAT (Janus kinases/signal transducers and activators of transcription) [87].…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines such as interleukin-1 (IL-1), IL-6, IL-8, and tumor necrosis factor alpha (TNF-a) have been found to be elevated in the sera of severely and critically ill COVID-19 patients, anti-inflammatory cytokines such as IL-10 have also been found in the sera of COVID-19 patients (13)(14)(15). Plasma IP-10, MCP-3 sTIM-3, HGF, IL-1a, IL-27, and PCT cytokines have also been reported to be related to the severity of the disease (16)(17)(18)(19). The profile of cytokine gene expression by cDNA arrays and protein arrays are widely used in different infectious diseases to identify biomarkers (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%